Ecotoxicology : effects of pollutants on the natural environment - Walker, C. H. (Boca Raton CRC Press, 2014)
"During the latter part of the 20th century chemical industry grew rapidly, and with this growth new industrial chemicals found their way into the natural environment. Pesticides came to be used on a larger scale, and questions were asked about residues of them that were found in environmental samples (biota, soil, water, and air). Residues were also found of a range of industrial chemicals in effluents entering rivers and polluted air. Some of these events received extensive media coverage, which was something of a mixed blessing. While important discoveries were made known to a wide audience, inaccuracies and half-truths crept into this reportage, sometimes leaving a rather confusing impression to interested laypeople. In time, government laboratories, industrial laboratories, and universities became involved in the investigation of pollution problems, and the discipline of ecotoxicology began to take shape. Today ecotoxicology courses are offered by universities and colleges of further education. While a number of textbooks are now available to students who follow ecotoxicology courses at universities and other institutions of higher education, there appears to be a shortage of texts aimed at interested laypeople. This seems unfortunate, because the science underlying environmental pollution has intriguing aspects to it. There is much evidence for the phenomenon of chemical warfare in nature, which, over a long period, has been a driving force in the evolution of plant toxins and the production by animals of systems that detoxify them. The selective pressure of pesticides has led to the evolution of resistant strains of pests. The biomagnification of recalcitrant organic pollutants in food chains has raised problems for predators of higher"--
Keywords: Environmental toxicology; Ecological risk assessment; Environmental chemistry; SCIENCE / Environmental Science; TECHNOLOGY & ENGINEERING / Environmental / General